Coupled Fixed Point with Mixed Weakly Monotone Property - Richa Sharma, Virendra Singh Chouhan, Deepti Sharma (International Journal of Advanced Science and Technology, 2020)
The main concern in this manuscript is to demonstrate coupled common fixed point result using structure of metric space adequate with a partial order. Utilizing the new property mixed weakly monotone, we generalize the result of Bhaskar and Lakshmikantham [1]. To support our result at the end, we provide an example.